French Osteotomy for Cubitus Varus in Children: A Long-term Study Over 27 Years. Issue 1 (January 2016) - North, David; Held, Michael; Dix-Peek, Stewart; Hoffman, E. B.
Abstract : Background: Cubitus varus is a cosmetically unacceptable complication of supracondylar fractures of the elbow in children. We have performed the lateral closing wedge (French) osteotomy to correct the varus for 27 years. More complex osteotomies have been described to correct the associated hyperextension and internal rotation deformities and to prevent a prominent lateral condyle. Methods: We retrospectively reviewed 90 consecutive patients (1986 to 2012). The mean age of the patients at surgery was 8.2 years (3 to14 y). The varus angle (mean, 21.4 degrees; range, 8 to 40 degrees) was assessed preoperatively with the humero-elbow-wrist angle. The postoperative carrying angle (mean, 10.4 degrees) and the preoperative and postoperative range of movement were assessed clinically. The lateral condylar prominence index (LCPI) was retrospectively measured at union. Results: Eighty-four (93.3%) of the patients had a good or excellent result. Six (6.7%) had a poor result (residual varus, loss of >20 degrees of preoperative range of flexion or extension or a complication necessitating resurgery). There were no neurovascular complications. The mean LCPI was +0.14. Conclusions: The results of the French osteotomy are comparable with the more technically demanding dome, step-cut translation, and multiplanar osteotomies, with a lower complication rate. The literature reports adequate remodeling of the hyperextension deformity (⩽10 y) and the LCPI (⩽12 y), and that the internal rotation deformity is well tolerated by the patient. Level of Evidence: Level IV—case series.